(untitled) (Medical Forum Monthly, 2024)
Objective: To examine efficacy of Risperidone for treatment of schizophrenia in comparison with placebo. Study Design: Randomized clinical study. Place and Duration of Study: This study was conducted at the Department of Psychiatry, Allied hospital, Faisalabad from May 2016 to May 2017. Materials and Methods: Approval of the study was taken from Ethical Review Board of the Allied hospital, Faisalabad. Data was collected through universal sampling technique and analyzed by using computer software SPSS version 22, mean and SD was calculated for quantitative variables like age and frequency (percentages) were calculated for qualitative variables like gender, education status and symptoms of disease. Chi square test was applied to see effect modification; p value ≤ 0.05 was taken as significant. Results: Total 80 respondents were included in this study, 24 (30%) were females and 56 (70%) were males and Placebo and Risperidone groups were equally distributed. Outcome of our study was improvement in symptoms of disease after drug use. From placebo group, almost all study participants were fall in condition not improved group (97.5%) and in Risperidone group more half (80%) study participants fall in condition improved group. Value of Chi square (49.6) at 1 degree of freedom was found statistically significant (0.000) indicating significant relationship of disease status and treatment group. Conclusion: Significantly greater improvements in relieving the symptoms and improving the quality of life and overall well-being were demonstrated in patients randomized to risperidone compared to placebo.